Communication as a tool for the public good in times of crises caused by the earthquakes in the City of Zagreb - Jurić, Tomislav (Crisis Management Days, 2025)
Urban environments are continuously exposed to a number of different types of threats and precisely as such become the sites of the gravest accidents and natural disasters throughout history (Bilandžić, 2019). In previous assessments of the risk of major accidents, which were performed for Zagreb in the form of a formal document even before such an obligation was established by the 2015 Act on the Civil Protection System, earthquakes have been identified as the greatest threat with possible catastrophic consequences. There are no available records of disasters of this type in the city’s past dating before the 16th century, and all those that had been made before the 19th century are considered less reliable because seismic intensity had not been officially evaluated. The magnitude of the strongest Zagreb earthquake to date, which occurred on 9 November 1880, was subsequently estimated at 6.3 on the Richter scale (Simović, 2000: 638). The catastrophic effects the earthquake had on the population are mostly evident from the print media, as well as the concrete and prompt responses of the city authorities to the crisis. An analysis of newspaper editions, which despite the destruction did not pause its publication, undoubtedly speaks to the high level of crisis management. On the same day the earthquake hit Zagreb, the Extraordinary Provisions of the City Government were published, the city was divided into specific areas, and a commission was sent to each of them with the task of assessing the effects of the earthquake. At the same time, the city prohibited the population from staying in buildings that were unsafe for habitation and prescribed specific signs to mark such premises. Available communication channels were also used to distribute appeals that, for safety reasons, prohibit or limit activities that pose a risk in that context. Telegrams were used as a means of communication to mobilize relevant experts, and there was intensive proactive communication among safety system stakeholders and the general public. Crisis management responded to the disinformation circulating in the public space with denials, and communication was maintained with remote and international centres. In the observed period after the accident, the media refrained from publishing unverified information and largely distanced themselves from unreliable sources, but due to a lack of photographic evidence, the texts contained strong descriptive elements. An article by August Šenoa, a renowned Croatian journalist and author, which, among other, stated that “journalistic madness did as much harm as the earthquake”, nevertheless suggested subsequent biased media portrayals of the event and its effects. Ten days after the earthquake, the city authorities introduced strict, even prison sentences, for publications that unfoundedly deepened the crisis or caused fear. Contrary to content created by non-experts, special newspaper articles informed citizens from a scientific perspective about the earthquake as a natural phenomenon (Šimetin Šegvić, 2020). Communication was continued in the post-crisis period, mainly on topics related to social and safety measures as well as detailed and precise information on restoration and reconstruction activities. The survey of citizens on their personal experience of the earthquake and its effects on individuals was conducted only eight days after the earthquake, and this procedure was considered the first macroseismic survey conducted in the Croatian language, which represented a strong contribution to science from a crisis point of view, with the application of communication techniques for research purposes (Faculty of Science and Mathematics, 2025). The institutionalization of the urban safety concept in Zagreb has been noticeable since 2005, when the responsibilities and tasks of defence as well as civil and natural disaster protection at the local level, i.e. protection and rescue, including fire protection, were systematized by the Mayor’s Office (Official Gazette 11/2025). A separate Emergency Management Office, the first of its kind in Croatia, which was assigned the responsibility for implementing prevention, handling and management measures during crisis situations, was established in 2008 (Official Gazette 2/2008). The importance of integrating the communication between key stakeholders in dealing with threats of varying intensities, which would simultaneously enable internal and two-way external exchange and distribution of important messages during crises, was reflected in the practical centralization of communication processes of the emergency, operational and technical, and on-call intervention authorities of the City of Zagreb through a project that was part of the so-called Holding Centre of the company Zagreb Holding wholly owned by the City of Zagreb (Zagrebački holding, 2018). In the crises that intertwined during 2020, brought about by the coronavirus epidemic and earthquakes, the concept significantly exceeded its original scope and functions and was considered a hub of multi-level communication in the crisis communication system. The justification for the presence of various communication tools and technologies was also confirmed outside the context of acute crisis situations; however, in the event of threats to critical communication infrastructure. The Holding Centre remained fully operational on 29 September 2020, when the telecommunications system collapsed throughout the country, which made it impossible for citizens to communicate with emergency services (HINA, 2020). The interruption of public telecommunications, which currently rely mostly on digital technologies and internet connections, had made mass communication difficult in the first moments of the crisis. It was implemented through official sources, media and social networks, but regardless of the channels and techniques used to transmit the messages, communication was not synchronized, structured and uniform. Contradictions were also noted, as was the presence of disinformation in the public space, and the analysis led to the conclusion that there was no functional protocol during the crisis response. Due to all of the above, it is reasonable to question whether the undeniable development of technology over the period of 140 years had necessarily ensured a better level of communication and management standards in crisis situations. 1 RESEARCH SUBJECT AND METHODS This paper investigates whether, in comparison with 1880, there had been an evolution in communication and operational activities related to earthquakes in the context of the crisis and post-crisis period, with a focus on the significance of crisis communication in the concept of urban safety and public good in the area of ​​the city of Zagreb. Its aim is to identify the level of efficiency and coordination of the system by comparing situations with the same or similar characteristics and the actions of the competent authorities, to highlight examples of good and desirable practices in terms of the safety system, as well as to determine the type and scope of activities that resulted in negative effects on the population in the crisis. In accordance with the above, the following hypotheses were set: H1: Zagreb applied high standards of crisis management and communication during the crisis caused by the 1880 earthquake H2: After the 1880 earthquake, public communication had the function of urban safety. H3: Compared to 1880, a positive step forward was recorded in crisis communication and management H4: Zagreb has modern channels and techniques for communication in crisis situations In order to achieve the set research objective, a number of qualitative methods were utilised, including the historical and research method, which reconstructs the chronological sequence of communication activities during crises. Relevant newspaper articles, official statements, regulations and archival materials were investigated using the content analysis method. Communication approaches and activities from two different time contexts were compared using the comparative method – the 1880 earthquake and the 2020 earthquake. Conclusions were drawn using the inductive and deductive method about the effectiveness of the crisis communication system in the historical context, and its development and possible shortcomings in the contemporary context. The description method was utilised to present the key communication activities during both crises, highlighting the key stakeholders, message content, communication channels and tools used. Also, a case study was applied as a qualitative method for a detailed description of specific situations that illustrate successful and unsuccessful communication practices. A comprehensive analysis of the quality and effectiveness of crisis communication has been ensured by combining the above methods, with the aim of formulating conclusions that can be used to improve future communication strategies in crisis situations in the area of ​​urban safety in the City of Zagreb. 2 PRINCIPAL CONCLUSIONS Crisis communication, as an element of crisis management, was comprehensive, planned and thorough during the crisis caused by the 1880 earthquake in Zagreb. Analysis of available archival material confirmed a high level of structured, timely and proactive communication, despite the technological limitations of that period. The city government introduced and publicly communicated specific safety instructions in a timely manner, using the then available channels such as the press and telegrams to inform the public, as well as the coordination of relevant authorities, which had a positive impact on controlling the effects of the earthquake and preventing additional damage. The institutionalization and integration of the concept of urban safety into public policies has led to a significant shift towards centralization and better integration of crisis communication in Zagreb, as well as compliance with the legislation and the activities of national authorities. Although communication discontinuity was recorded in the early stages during the 2020 earthquake, the aforementioned authorities significantly contributed to better coordination of activities in the restoration period that followed. Crisis communication during the 2020 earthquake was made difficult by the partial collapse of digital communication channels immediately after the earthquake, partial message inconsistency, and the flow of disinformation in the public space. The above points to the importance of continuous maintenance and protection of critical infrastructure and the necessity of alternative communication channels during crisis situations. The research results indicate that continuous and systematic communication, which includes educating the population about the nature of crisis situations, significantly contributes to the effectiveness of crisis management and points to the necessity of investing in preventive informing of citizens and education about crisis protocols. In conclusion, a comparison of historical and contemporary experience shows that effective crisis communication needs to be timely, coordinated, and focused on message clarity, while technical preparedness and clearly defined communication protocols are key elements that can significantly mitigate the consequences of crisis events such as earthquakes.